Banglapedia national encyclopedia of Bangladesh. - Islam, Sirajul, 1939-; Asiatic Society of Bangladesh (Dhaka : Asiatic Society of Bangladesh, 2004)
Banglapedia furnishes data, images, video clips, audio clips, facts and information about all branches of knowledge concerning Bangladesh-including history and heritage, arts and humanities, society and economy, state and polity, ideas and institutions, philosophies and sciences, nature and environment.
Title from disc label.
"Board of Editors Chairman, Professor Sirajul Islam"--Introd.
"February 2004."
Also issued in print and the World Wide Web.
System requirements: Pentium based IBM-PC or compatible; 32MB RAM; Windows 98/ME/2000/XP/NT 4; Microsoft Internet Explorer 4, or compatible Web browser; 6MB free hard disk space; 4X CD-ROM drive; 26-bit graphic display, or better; 16-bit sound support.
Keywords: Bangladesh -- Encyclopedias